Spectral data of nicotabaflavonoidglycoside - Cai-Yan Yang; Yao Lin; Hui-Xiong Yuan; Wen-Pei Yang; Xian Wei; Zu-Liang Huang (Data in Brief, 2018)
The dataset addressed in this article relates to the research article entitled“Nicotabaflavonoidglycoside, the first example of cembranoid and flavonoid heterodimer from Nicotiana tabacum” (Yang et al., 2018) [1]. The dataset presents the MS4(879-571-421-335), MSn fragment pathways, (+) HR-ESI-MS, (−) HR-ESI-MS, UV, IR, 1H NMR, 13C NMR, HSQC, 1H–1H COSY, HMBC, ROESY, ORD and ECD data of Nicotabaflavonoidglycoside. The MS4(879-571-421-335), (+) HR-ESI-MS, (−) HR-ESI-MS, UV, IR, 1H NMR, 13C NMR, HSQC, 1H–1H COSY, HMBC, ROESY, ORD and ECD data were collected by experimental methods, and the MSn fragment pathways were acquired by analyses.